Cover Image, Volume 11, Issue 2. (2nd March 2017) - Ge, Shijian; Champagne, Pascale; Plaxton, William C.; Leite, Gustavo B.; Marazzi, Francesca
Abstract : The cover image, by Shijian Ge et al., is based on the Review Microalgal cultivation with waste streams and metabolic constraints to triacylglycerides accumulation for biofuel production, DOI:10.1002/bbb.1726 . Abstract : The cover image, by Shijian Ge et al., is based on the Review Microalgal cultivation with waste streams and metabolic constraints to triacylglycerides accumulation for biofuel production, DOI:10.1002/bbb.1726 .